Dynamical Analysis of a Delayed SIQS Epidemic Model on Scale-Free Networks (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we establish a novel delayed SIQS epidemic model onscale-free networks, where time delay represents the average quarantine period.Through mathematical analysis, we present the basic reproduction number $R_0.$ Then, we provide the global asymptotical stability of the disease-freeequilibrium and the local asymptotical stability of the endemic equilibrium.Finally, we perform numerical simulations to verify the correctness of the mainresults and analyze the sensitivity of parameters. Our research shows thatwhen $R_0 > 1,$ lengthening the quarantine period can slow the spread of thedisease and reduce the number of infected individuals.
Keywords: Epidemic model; Network; Quarantine period; Stability.